Radiografi Antegrade Pyelography dengan Sangkaan Hydronefrosis d RSUPH. Adam Malik Medan - Ariyanti, Stephanie; Br Pinem, Ester (Health Information : Jurnal Penelitian, 2023)
Antegrade Pyelography is a technique or procedure for X-ray examination of the upper urinary system by inserting a contrast medium which is inserted through the renal system (calyces). Contrast media is inserted through a nephrostomy catheter which has previously been installed by a urologist surgically. Hydronephrosis is distention of the renal pelvis and calyces of the kidney resulting from some obstruction of the ureter or renal pelvis. This study aims at a non-functional examination of the urinary system in which contrast medium is inserted directly antegrade into the pelvicalyceal system via catheterization by a urologist during a minor surgical procedure. This procedure is often performed to determine the location of urinary tract stones or other types of obstruction. The examination is antero-posterior and oblique. Research on Antegrade Pyelography radiography with suspected Hydronephrosis, this type of research uses qualitative research. Antegrade Pyelography examination with suspected Hydronephrosis at the H. Adam Malik Central General Hospital in Medan using a General Purpose to study in more depth the knowledge that has been obtained during lectures and to see abnormalities in Antegrade Pyelography. This research was carried out at the H. Adam Malik Central RSU Medan on June 14 2021, using qualitative methods, Observation, Interview, Consultation and Documentation.